Synthesis, characterization, X-ray crystal structure and DFT calculations of 4-([2,2':6',2''-terpyridin]- 4'-yl)phenol - Cesar Sierra; Brian Castro Agudelo; Cristian Ochoa-Puentes; William Rodriguez-Cordoba; Andreas Reiber (Revista Colombiana de Química, 2018)
The synthesis of new terpyridine (Tpy) derivatives has been subject of extensive research due to its potential as functional materials for solar energy conversion, among other applications. In this contribution, the 4-([2,2':6',2''-terpyridin]-4'-yl)phenol (TpyOH) has been synthesized, characterized and studied through several methods, including X-ray crystallography and computational approaches. Single crystal X-ray structure analysis shows that TpyOH is essentially planar, with dihedral angles of about 5.03° between the central pyridinyl and the phenolic ring, and also 6.05 and 12.2° in the terpyridine moiety. In the crystal, molecules are linked by intermolecular hydrogen bonds and through π-π stacking interactions. Using a time-dependent density functional theory approach and taking into account bulk solvent effects, the absorption and fluorescence spectra of TpyOH were investigated and compared. The TD-DFT S0→Sn and S1→S0 transition energies are in good agreement with experimental results. The frontier molecular orbitals analysis showed that the low-energy absorption band has an intraligand charge transfer character (ICT), while the high-energy band is a common feature of π-π* transitions of the Tpy moiety. The S1→S0 emission transition also has an ICT character, with a 90% contribution from the HOMO→LUMO transitions.